2008
DOI: 10.1161/circulationaha.107.761965
|View full text |Cite
|
Sign up to set email alerts
|

Torcetrapib Does Not Reduce Atherosclerosis Beyond Atorvastatin and Induces More Proinflammatory Lesions Than Atorvastatin

Abstract: Background-Although cholesteryl ester transfer protein (CETP) inhibition is regarded as a promising strategy to reduce atherosclerosis by increasing high-density lipoprotein cholesterol, the CETP inhibitor torcetrapib given in addition to atorvastatin had no effect on atherosclerosis and even increased cardiovascular death in the recent Investigation of Lipid Level Management to Understand its Impact in Atherosclerotic Events trial. Therefore, we evaluated the antiatherogenic potential and adverse effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 35 publications
5
63
3
3
Order By: Relevance
“…Nevertheless, the apparent trend of decreasing risk with increasing atorvastatin dose for both endpoints, combined with a lack of imbalance in other predictors that would explain the result, is consistent with the proposition that higher doses of atorvastatin may have protected against the adverse effects of torcetrapib via properties of the drug unrelated to the lowering of LDL-C ( 5 ). These results do not support the proposition, suggested by others ( 6 ), that addition of higher doses of atorvastatin may have interacted adversely with torcetrapib, because in this case, the opposite relationship with atorvastatin dose would have been observed. Nor does the analysis support the proposition that the adverse effects of torcetrapib were the consequence of the observed changes in blood pressure, concentrations of plasma lipoproteins, electrolytes, or CRP.…”
Section: Discussioncontrasting
confidence: 93%
“…Nevertheless, the apparent trend of decreasing risk with increasing atorvastatin dose for both endpoints, combined with a lack of imbalance in other predictors that would explain the result, is consistent with the proposition that higher doses of atorvastatin may have protected against the adverse effects of torcetrapib via properties of the drug unrelated to the lowering of LDL-C ( 5 ). These results do not support the proposition, suggested by others ( 6 ), that addition of higher doses of atorvastatin may have interacted adversely with torcetrapib, because in this case, the opposite relationship with atorvastatin dose would have been observed. Nor does the analysis support the proposition that the adverse effects of torcetrapib were the consequence of the observed changes in blood pressure, concentrations of plasma lipoproteins, electrolytes, or CRP.…”
Section: Discussioncontrasting
confidence: 93%
“…However, APOE*3Leiden mice (like WT mice) do not possess a CETP gene, and therefore these mice do not respond to HDL-modulating interventions. By crossbreeding the APOE*3Leiden mice to mice expressing the human CETP gene ( 75 ), APOE*3Leiden.CETP mice were obtained that respond to both lipid-lowering as well as HDL-raising interventions (50)(51)(52)(53)76 ). In the current study, we found signifi cant lowering effects of anti-PCSK9 antibodies on TC and TG levels in APOE*3Leiden.CETP mice, but HDL-C was not affected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The APOE*3Leiden.CETP mice are a well-established mouse model for familial dysbetalipoproteinemia with human-like lipoprotein metabolism and atherosclerosis development, which respond in a human-like manner to both lipid lowering as well as HDLraising drugs (like statins, fi brates, niacin, etc.) used in the treatment of CVD (49)(50)(51)(52).…”
Section: In Vivomentioning
confidence: 99%
“…However, although the HDL elevating effect of statins is marginal on the average, statins may be benefi cial for improvement of HDL in a subset of women with high score LDL + HDL. Such an effect could be important, considering that a higher HDL level after 3 months of statin treatment has been shown be associated with protection from major cardiovascular events ( 50 ) and since novel therapies developed to increase HDL did not lead to an overall benefi t on endpoints (51)(52)(53)(54).…”
Section: Power Calculationsmentioning
confidence: 99%